Analisis Geospasial Berbasis Pemodelan Geofisika: Kuantifikasi Disparitas Distribusi Fasilitas Pendidikan Menggunakan metode NNA dan Buffer Di Kecamatan Samarinda Ulu - Warda Nur Rasya; Oktavianus Claudio; Salma Asy-Syifa; Nanda Khoirunisa (Progressive Physics Journal, 2026)
Spatial inequality in educational access represents a critical issue that requires an objective and measurable geophysical approach. This study applies geophysical modeling through the Nearest Neighbor Analysis (NNA) and Buffer methods based on Geographic Information Systems (GIS) to analyze the spatial distribution patterns of educational facilities in Samarinda Ulu District, Samarinda City. Spatial data from 66 educational institutions (33 elementary schools, 17 junior high schools, and 15 senior high/vocational schools) serving 21,349 students were analyzed using ArcGIS version 10.8. The NNA technique considered parameters such as inter-location distance, facility point density, and administrative area size. The quantitative analysis revealed a spatial significant clustered pattern (NNA index < 1.0), indicating a non-uniform spatial concentration of educational facilities. The Buffer analysis further identified disparities in Air Hitam and Bukit Pinang subdistricts. Geospatial analysis delineated two contrasting zones: a high-access zone in Air Putih (30,249 residents) and Gunung Kelua (13,630 residents) with an educational facility density 2.3 times higher than the low-access zone in Bukit Pinang (12,160 residents). This spatial disparity creates an average travel distance gap of 3.2 km for students in underserved areas, affecting both accessibility and educational equity. The findings provide empirical, geophysics-based evidence of unequal educational facility distribution, serving as a foundation for optimizing educational infrastructure planning. The resulting spatial model recommends the addition of new school units in deficit zones, prioritizing development along the Bukit Pinang–Dadi Mulya corridor to achieve a more balanced distribution. This research contributes to the advancement of applied geophysical methodologies for urban planning and may serve as a policy reference for local governments to promote equitable educational access based on quantitative spatial analys